A scale based approach to jazz improvisation over dominant 7th chords / Wahi Hidayat Ramli - Ramli, Wahi Hidayat (2011)
Since in the early 20th century, jazz has become a major influence on all type of music, dance, and related arts throughout the world. A study of improvisation is common for musician, teacher or student in jazz .The rhythm, articulation, and phrasing used in jazz improvisation evolve from the individual's interpretation of what is placed on the page or heard to transfer to an instrument. A dominant 7th chord has the biggest function in jazz for example as a secondary dominant, a triton, an ,altered dominant and the learning and understanding the chords itself is very important in both Jazz improvisation and composition and also a link to major or minor chord. The basic tool in jazz harmony is scale for application in jazz improvisation over dominant7th chord. Thus, the aim ofthis research is only to determine what scales can be used as a vehicle for improvisjltion over a dominant chord and its function to major and to minor and why these scales can be used over it. By done this, the interview session need to be conduct and data from the research were collected through interview. An analysis of scales in jazz solo transcription over dominant7th chord also is needed to prove the scale relations ship with dominant7th to major or minor chord and why it used by that artist. The analysis and discussion ofthis research are attached in this thesis and a concluding remark is made.